"Role Efficacy" of Teachers at Polytechnics and its Development:A Survey - Anand, Y. K. (Journal of Engineering Education Transformations, 1995)
Teachers hold a pivotal position in polytechnics. Their performance in this position is dependent on their personality, competency, experience and organizational climate in the polytechnic. The type and content of role assigned to them also affects their performance and effectiveness. Some teachers extend/modify/change their role in accordance with their personal need, get job satisfaction and thus perform better compared to those who stick to the role assigned to them by higher ups. The paper presents findings of a study undertaken to get opinion of teachers of polytechnic about effectiveness of their organizational role and make suggestions for improvement in it for satisfying their need. This study was conducted by administrating "Role Efficacy Scale" by Pareek (1) and Personal Profile Proforma to a group of 22 teachers of the polytechnic of a State of Northern part of India. The findings of study offer a new insight into the thinking of teachers about their present role and suggest initiatives needed at management and individual level for making it more effective.